2000
DOI: 10.1046/j.1365-2141.2000.02091.x
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of elevated factor VIII antigen levels in factor V Leiden families with thrombophilia

Abstract: Summary. Factor VIII activity (factor VIII:C) and factor VIII antigen (factor VIII:Ag) levels above150 IU/dl are associated with a five-to sixfold increased risk of venous thrombosis compared with levels , 100 IU/dl. These high levels are present in 25% of patients with a first episode of deep-vein thrombosis and in 11% of healthy controls. von Willebrand factor (VWF) and blood group are important determinants of the factor VIII level in plasma and therefore contribute to thrombotic risk, while factor VIII app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 13 publications
2
47
1
1
Order By: Relevance
“…Hemophilias are disorders with loss of protein function, whereas gain of function (high concentrations of factors VIII or IX) has been linked to thrombophilia. 31,32 High factor VIII levels aggregate in families, 33 pointing towards a genetic origin. However, this genetic disorder is apparently not sex linked and thus cannot explain the absence of detectable genetic effects among females in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Hemophilias are disorders with loss of protein function, whereas gain of function (high concentrations of factors VIII or IX) has been linked to thrombophilia. 31,32 High factor VIII levels aggregate in families, 33 pointing towards a genetic origin. However, this genetic disorder is apparently not sex linked and thus cannot explain the absence of detectable genetic effects among females in our study.…”
Section: Discussionmentioning
confidence: 99%
“…46 Analysis of familial aggregation of factor VIII levels Ն150 IU/dL in 12 large thrombophilic families 57 identified blood group as the main determinant: 86% of the subjects with factor VIII levels Ն150 IU/dL had blood group non-O. However, after adjustment for blood group and age, factor VIII levels Ն150 IU/dL still aggregated in these families.…”
Section: Determinants Of Plasma Factor VIII Levels Genetic Determinanmentioning
confidence: 99%
“…For high levels of factor VIII, it has been shown that there is familial clustering of high levels, even when the blood group effect has been taken into account. 79,80 Thrombosis as a Multicausal Disease Many risk factors for thrombosis known today are common in the general population, and therefore several will often be present in one individual. Acquired risk factors also have a high prevalence, and therefore a combination of several genetic and several acquired risk factors in one individual may not be infrequent.…”
Section: High Levels Of Clotting Factorsmentioning
confidence: 99%